Modeling of the Symptom Manifestation of Personality Disorders in Nursing Students and Temporary Nurses within the Human Research Project Based on Childhood Trauma and the Mediating Role of Emotional Cognitive Regulation - MA Ghodratollahifard; M Chinaveh; S Aminimanesh (Iran University of Medical Sciences, 2020)
Background & Aims: According to the World Health Organization (WHO) statistics, millions of children are victims of abuse each year. Childhood trauma could be physical or psychological abuse, sexual abuse or neglect of a child by the guardian. Abuse has long-lasting and irreversible effects on the psyche of children, which may linger even through adulthood. Among the long-term psychological effects of childhood abuse are major behavioral and psychological disorders in adolescence and adulthood. Such an example is the onset of the symptoms of cluster C personality disorders, which encompass avoidant, dependent, and obsessive-compulsive personality disorders, commonly characterized by anxiety, apprehension, and fear in the affected individuals. Cognitive emotional regulation is a variable that may be influenced by childhood trauma and lead to symptoms of personality disorders. Emotional regulation refers to the process through which an individual recognizes the emotions that are affecting them, how to experience these emotions, and their management. Recent findings suggest that even when child abuse is controlled, the problems associated with emotional regulation persist. Nurses constitute the largest portion of healthcare providers and affect the productivity and progress of the organization more than other hospital staff. In addition, the productivity of nurses ultimately leads to better decision-making in planning healthcare services. Therefore, assessing the predispositions of personality disorders in nursing students and temporary nurses within the program of human research project is paramount. One of these preconditions is the childhood traumas of the nursing students and temporary nurses within the program of human research project . The present study aimed to propose a model of childhood trauma and cognitive emotional regulation to help recognize cluster C personality disorders in the nursing students and temporary nurses within the program of human research project in 2019. Materials & Methods: This cross-sectional, descriptive-correlational study was conducted on the nursing students of Shiraz University of Medical Sciences in 2019 and the temporary nurses within the program of human research project in Shiraz, Iran. The inclusion criteria were consent to participate in the research, no history of psychological treatments for emotional disorders, no use of psychiatric medications for the reduction of anxiety, stress, and depression, living with parents, absence of specific chronic disorders affecting physical and mental health (e.g., migraine, severe lower back pain, diabetes, cardiac and renal diseases, and infertility), and normal course of life within six months before the investigation (i.e., no specific incidents or crisis such as the death of a loved one, an incurable disease of a family member, and change of residence). The subjects with incomplete questionnaires and those using psychiatric medications were excluded from the study. Data were collected using the self-report early trauma inventory-short form, cognitive emotion regulation questionnaire, and Millon clinical multiaxial inventory-III, which was completed in a self-report manner. During the completion of the questionnaires, the researcher, who was experienced in mental illness counseling, accompanied the participants to gain their trust and address their concerns in responding to the questions. The sample size of the study included 291 nursing students and employed nurses, which was estimated using the G-power software. The subjects were selected via simple cluster sampling. After providing the necessary explanations regarding the importance of the research and attracting sincere cooperation, the questionnaires were distributed among the students and nurses. Considering individual differences, the set time for the completion of the questionnaires was 15-30 minutes, and the questionnaires were received after completion. Data collection continued for one week and was performed at the hospital for the temporary nurses within the program of human research project with the coordination of the supervisor and at the nursing school for the senior nursing students. Data analysis was performed in SPSS version 22 using Pearsonchr('39')s correlation-coefficient to describe and analyze the statistical data. In addition, the AMOS-22 software was applied to determine the fit of the studied model based on the structural equation model and analyze the path of the observable variables. Notably, all the calculations were carried out at the statistical inference limit of P<0.05. Results: Childhood general traumas, childhood physical abuse, and childhood sexual abuse could explain the obsessive-compulsive disorder in the nursing students both directly (P<0.01, P<0.0005, and P<0.0005, respectively) and indirectly through adaptive and maladaptive cognitive emotional regulation styles (P<0.01). Moreover, childhood physical abuse could explain the avoidant personality disorder of the students both directly (P<0.05) and indirectly through adaptive and maladaptive cognitive emotional regulation styles (P<0.05). Childhood physical abuse and childhood sexual abuse could explain the dependent personality disorder of the students both directly (P<0.001 and P<0.05, respectively) and indirectly through maladaptive cognitive emotional regulation styles (P<0.05). The statistical findings also indicated that the obtained data supported the theoretical model of explaining personality disorders to a great extent, and all the indicators of fit confirmed that the proposed model is acceptable. Conclusion: According to the results, the senior nursing students and employed nurses within the program of human research project who have been abused as children were more likely to present with symptoms of cluster C disorder in their behaviors in adulthood. Furthermore, cognitive emotional regulation strategies acted as a mediating variable in the association of childhood trauma and cluster C personality disorder; in other words, childhood trauma leads to emotional maladjustment in adulthood, and the lack of appropriate emotional regulation strategies could lead to the symptoms of cluster C personality disorder. Based on the findings, it is expected that training on cognitive emotional regulation strategies would act as an effective mechanism in the modification of cognitive emotional regulation and become an proper approach to the improvement of cluster C personality disorders in nursing students and employed nurses within the program of human research project, thereby preventing mental illnesses and personality disorders.